Vocal resonance technique of 'Selve Amiche, Ombrose Piante' by Cecilia Bartoli / Nur Faqihah Aliah Zubaidi - Zubaidi, Nur Faqihah Aliah (2022)
This paper aims to investigate the different types of vocal resonance technique that could be applicable in singing. The prominent features of vocal resonance technique could emphasize singers the importance of developing resonance in any singing style especially on classical singing. The purpose of this research as a contribution on comprehension for singers the importance of developing resonance functioning in singing which are needed to be understood in a proper way of use and how it is functioning in singing especially in classical piece. The objectives of this research study are to ascertain the types of vocal resonance technique that naturally formed in a human organ and vocal apparatus and to investigate the effectiveness way use of resonance technique development by Cecilia Bartoli on "Selve Amiche, Ombrose Piante" on certain phrases in this piece.